Rancang Bangun Aplikasi Pendukung Penentuan Susunan Bahan Makanan Bagi Diabetisi Pada Poli Gizi RSUD Dr.Soetomo Surabaya - Faudi, Bayu Rachmanda; Nurcahyawati, Vivine; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Diabetus Mellitus (DM) is a chronic disease that is increasing from year to year. Patients with diabetes mellitus (diabetes) type 2 can be treated with appropriate dietary adjustments. In determining the composition of foodstuffs are still awaiting laboratory data with diabetes and the calculation process composition of foodstuffs still run manually so it takes a long time. This causes parts of poly nutrition requires a medium to help speed up the process of determining the composition of food for people with diabetes. Based on the above problems, the solutions that can be done is to create an application that can assist in determining the composition of poly nutritional food for people with diabetes. VB.Net based applications used by using SQL Server database. This application requires a diabetes blood test results, then the system will result in the determination of the composition of food for those with diabetes. The results showed that poly-party applications can help to support the determination of the nutritional composition of foods for people with diabetes is. As evidenced by the results of experiments conducted to 10 people with diabetes with the result of improved data accuracy of 20%, improved speed of 9.78 minutes and the data relevant to 40%. This application can also provide information about the composition of foodstuffs along with taboo food for people with diabetes Keywords: Pola Makan, Diabetus Mellitus, Poli Gizi